A comprehensive analysis of three-dimensional normal grain growth of pure iron via multi-phase field simulation - Mao H.; Li B.; Du Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
A three-dimensional (3D) multi-phase field model was established to simulate normal grain growth in pure iron. The advanced visualization technology was used to extract the related data for individual grains, which can clearly display the grain morphology with distinct grain boundary surface as well as the space distribution of neighboring grains．Based on the simulation results, the grain growth kinetics model was described, which is in conformity with Burke and Turnbull’s parabolic law. The phenomenon of a ‘Hillert regime’ in 3D grain growth and the topological transformation mechanism were investigated. The grain size distributions under different time evolution showed a good agreement with the Hillert distribution. The details of grain growth, especially grain size distribution and volume growth rate, were analyzed. The models of von Neumann-Mullins and Hilgensfeldt for predicting the volumetric growth rate were compared. The volumetric growth rate was approximately zero when the number of grain sides was close to 13.7. The multi-phase field simulation can be used to analyze the dynamic evolution of the topological relationship of grains and reveal the general law of normal grain growth quantitatively.